Strategi Humas KPAI dalam Melaksanakan Tugas Pengawasan pada Kasus Bullying Terhadap Guru, Januari-April, 2019 - wina puspita sari; Fildzah Hani Mufidah (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2020)
ABSTRACT November 2018, there was 1 report on the occurrence of bullying against teachers, then at the beginning of 2019, precisely January-April increased to 4 reports, the authors were interested in reviewing how the KPAI Public Relations Strategy can reduce the increase in bullying rates in carrying out supervisory tasks in bullying cases against teachers. This study aims to identify the KPAI Public Relations strategy in Carrying Out Supervision Tasks towards increasing cases of bullying against teachers. This research uses a qualitative research approach with descriptive methods. The author uses various sources in collecting data such as interviews, observations, and documentation involving 1 key informant and 2 informants. KPAI's Public Relations Strategy in Carrying Out Supervisory Tasks in the Case of Bullying Against Teachers, namely: strategy of publicity in the form of press conferences, strategy of persuations with cooperation built with various other parties such as regional Child Protection Commission (KPAD), Integrated Service Center for Empowering Women and Children (P2TP2A), and the Regional Technical Implementation Unit (UPTD), strategy of argumentation in the form of Publication in Social Media and Preaching to the Mass Media positively as a rival, and strategy of image by displaying environmental and social concern as an institution that is fast and responsive to every the case that was filed in the complaint. The conclusion of this research is that KPAI Public Relations uses the publicity and publication of the KPAI Public Relations Strategy in monitoring bullying cases against teachers. Publication on Social Media and News on websites, press conferences. While the role and efforts of KPAI Public Relations Guard the case & summarize the recommendations, Cooperate with other parties, and give a reprimand. Keywords: PR Strategy, Bullying, Teachers. ABSTRAK November tahun 2018, masuk 1 laporan terjadinya bullying terhadap guru, lalu di awal tahun 2019 tepatnya Januari-April meningkat menjadi 4 laporan, maka penulis tertarik untuk mengkaji bagaimana Strategi Humas KPAI dapat menekan naiknya angka bullying dalam melaksanakan tugas pengawasan pada kasus bullying terhadap guru. Penelitian ini bertujuan mengidentifikasi strategi Humas KPAI dalam Melaksanakan Tugas Pengawasan terhadap meningkatnya kasus bullying terhadap guru. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan metode deskriptif. penulis menggunakan berbagai sumber dalam pengumpulan data seperti wawancara, observasi, dan dokumentasi dengan melibatkan 1 key informan dan 2 informan. Strategi Humas KPAI dalam Melaksanakan Tugas Pengawasan pada Kasus Bullying Terhadap Guru, yaitu : strategy of publicity berupa kegiatan konferensi pers, strategy of persuations dengan kerjasama yang dibangun kepada berbagai pihak lain seperti Komisi Perlindungan Anak daerah (KPAD), Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A), dan Unit Pelaksana Teknis Daerah (UPTD), strategy of argumentation berupa Publikasi di Sosial Media dan Pemberitaan kepada Media massa secara positif sebagai tandingan, dan strategy of image dengan menampilkan kepedulian terhadap lingkungan dan sosial sebagai lembaga yang cepat dan tanggap akan setiap kasus yang masuk di pengaduan. Kesimpulan dari penelitian ini Humas KPAI menggunakan publisitas dan publikasi Strategi Humas KPAI dalam pengawasan kasus bullying terhadap guru. Publikasi di Sosial Media dan Pemberitaan di website, konferensi pers. Sedangkan peran dan upaya Humas KPAI Mengawal kasus & merangkum rekomendasi, Bekerjasama dengan pihak lain, dan Memberikan teguran. Kata Kunci: Strategi Humas, Bullying, Guru.